ANALISIS MODEL PEMBELAJARAN AQIDAH AKHLAK DALAM PENGEMBANGAN KEMAMPUAN ANALITIS SISWA KELAS VII DI MTS SUMBERSARI KOWANG - Sisfiana Ajeng Anggraeni; Dwi Ertina Wati (CV. Adiba Aisha Amira, 2026)
The development of analytical ability is an essential aspect of higher-order thinking skills that must be fostered through Islamic education, particularly in Aqidah Akhlak learning. However, learning practices in many madrasahs remain dominated by conventional methods emphasizing memorization rather than analytical reasoning. This study aims to analyze the Aqidah Akhlak learning model and its role in developing the analytical abilities of seventh-grade students at MTs Sumbersari Kowang. This research employed a qualitative descriptive approach. Data were collected through in-depth interviews, participatory observation, and documentation involving teachers, students, and the school principal. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing. The findings indicate that the implementation of case-based learning combined with group discussions and role-playing effectively enhances students’ analytical abilities. Students demonstrated improved skills in identifying moral problems, analyzing Islamic textual evidence, constructing logical arguments, and making ethical decisions. Classroom participation increased from 50% to 80%, while students’ essay scores improved from an average of 70 to 85. This study concludes that the Aqidah Akhlak learning model is effective and relevant for developing students’ analytical abilities in madrasah contexts, particularly in rural areas.